2019
DOI: 10.1002/advs.201800815
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Sulfur Transformation by Multifunctional FeS2/FeS/S Composites for High‐Volumetric Capacity Cathodes in Lithium–Sulfur Batteries

Abstract: Lithium–sulfur batteries are currently being explored as promising advanced energy storage systems due to the high theoretical specific capacity of sulfur. However, achieving a scalable synthesis for the sulfur electrode material whilst maintaining a high volumetric energy density remains a serious challenge. Here, a continuous ball‐milling route is devised for synthesizing multifunctional FeS 2 /FeS/S composites for use as high tap density electrodes. These composites demonstrate a maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
94
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(103 citation statements)
references
References 52 publications
(116 reference statements)
7
94
0
2
Order By: Relevance
“…[ 10 ] Furthermore, TMSs are favorable in achieving fast ion/electron transfer process for sulfur cathode owing to its high conduction properties. [ 11 ] Therefore, a selection of sulfur host material with decent ion/electron conduction, proper structural design with enhanced structural stability and abundant LiPS trapping/catalytic active sites is essential in the development of high‐performance Li–S batteries.…”
Section: Introductionmentioning
confidence: 99%
“…[ 10 ] Furthermore, TMSs are favorable in achieving fast ion/electron transfer process for sulfur cathode owing to its high conduction properties. [ 11 ] Therefore, a selection of sulfur host material with decent ion/electron conduction, proper structural design with enhanced structural stability and abundant LiPS trapping/catalytic active sites is essential in the development of high‐performance Li–S batteries.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond that, some special chemical reactions can also be triggered by ball milling method to achieve new sulfur‐based composite cathodes. Xi et al [ 81 ] reported a simple ball milling method to synthesize multifunctional FeS 2 /FeS/S as LSBs cathode with high tap density. The redox reaction between Fe 3+ and S x 2− was achieved with consecutive ball‐milling process.…”
Section: Sulfur‐based Cathode Materials: Methods Problems and Solutmentioning
confidence: 99%
“…6,7 However, the insulativity of active sulfur and discharge product (Li 2 S), the solubility of discharge intermediates (Li 2 S x , 4 ≤ x < 8) into organic electrolyte, and the "shuttle effect" by diffusing polysulfides into the negative electrode to produce parasitic reactions, cause serious active sulfur loss from cathode and cycle deterioration of the batteries, greatly hindering the Li-S batteries' development and commercialization. [8][9][10] In order to address these issues, significant progresses have been made in the last decade by immobilizing sulfur within various host materials to form sulfur-based composites, like sulfur/carbon composites, [11][12][13][14][15][16][17][18] sulfur/metallic compounds composites, [19][20][21][22][23][24][25][26] and sulfur/polymer composites. [27][28][29][30][31] It is noted that among the various host materials, microporous carbon is quite distinctive, because esterbased electrolyte was usually used for sulfur/microporous carbon (S/MC) composites based Li-S batteries, while ether-based electrolyte was commonly used in other composites based Li-S battery systems.…”
Section: Introductionmentioning
confidence: 99%
“…In order to address these issues, significant progresses have been made in the last decade by immobilizing sulfur within various host materials to form sulfur‐based composites, like sulfur/carbon composites, sulfur/metallic compounds composites, and sulfur/polymer composites . It is noted that among the various host materials, microporous carbon is quite distinctive, because ester‐based electrolyte was usually used for sulfur/microporous carbon (S/MC) composites based Li‐S batteries, while ether‐based electrolyte was commonly used in other composites based Li‐S battery systems.…”
Section: Introductionmentioning
confidence: 99%